Anonymous
Anonymous asked in Science & MathematicsMathematics · 9 years ago

# help with this problem i'm stuck...?

Solve using the elimination method. Show your work. If the system has no solution or an infinite number of solutions, state this.

-3x+4y=1, -6x+6y=-3

So this is what i got--- multiply -2 to the first equation gives me -6x+8y=1..... then combine the 2 equation-6x+6y=-3 i get -12x+16y=-2 now what do i do..

Relevance
• 9 years ago

You didn't have to muiltyply the 2nd line by 2...

you have

-6x + 8y=-2 [Muilty the whole thing by -2 even the anwser]

-6x + 6y=-3 [Leave the 2nd eqation alone]

2y=1 [Forget about the xs they now cancel each other out and subtract the rest of the eqation]

y=2 [Divide 2]

TO find the x you subsite the y and pick any of the 2 ORGINAL eqations

3x + 4y =1

3x + 8 =1 [Y=2 times that by the 4]

3x =-7 [Subtract the 8]

x=2.333333333333333333333333333 [Divide by 3]

If you're not sure that you got it right you can plug in both anwsers to see if it's true

-3x + 4y = 1

-7 + 8 = 1 [Substute the x and y vaules and muiltiply I also rounded 6.999999 to 7]

1 = 1 [The values match so I'm right]

• 9 years ago

multiply by -2 gives you +6x - 8y = -2. Combine and you get 6x - 6x +6y -8y = -2 -3 or -2y = -5 which means y = 5/2. Substitute his value into the first equation and you get -3x + 4*(5/2) = 1 or -3x + 10 = 1

or -3x = -9 which means x = 3.

• 9 years ago

First mult first definition by -2

6x - 8y = -2

-6x+6y = -3

0x - 2y = -5

y = 2.5

and then -3x + 4(2.5) = 1

-3x + 10 = 1

-3x = -9

x = 3

so answer would be (3, 2.5)

• 9 years ago

what you want to do is eliminate ONE of the variables.

1. Multiply -2 to the first equation -> 6x-4y= -2

2. Then line them up like this: 6x - 4y= -2

-6x+ 6y= -3

3. Add them up. 6x + -6x=0, -4y + 6y= 2y, -2 + -3 = -5

4. the equation that you end up with is: 2y=-5

5. Solve for y.

6. Plug in the number you get for y in the first (or second) equation.

7. Solve for x.

Voila!

I'm not going to do all of it for you, so you have to do the actual math...

Source(s): Knowledge.
• Anonymous
9 years ago

Multiply the first equation by -2.

-2(-3x+4y)=-2(1)

6x-8y=-2

6x -8y=-2

-6x+6y=-3

---------------

-2y =-5

-2y=-5

y=5/2

Then plug in the value of y into either of the two original equations.

-3x+4y=1

-3x+4(5/2)=1

-3x+10=1

-3x=-9

x=3